THE CONCEPT OF FINANCIAL STABILITY OF INSURANCE COMPANIES AND ITS THEORETICAL BASIS - Khakberdiyev Bekzod Uktamovich (American Journals, 2024)
This article discusses the issues of improving the practice of ensuring the financial stability of insurance companies, and discusses the scientific and theoretical views of foreign and domestic economists on the development of the insurance market and ensuring the financial stability of insurance companies. It also covers the classification of financial stability of insurance companies and factors affecting the financial stability of insurance companies. In addition, practical conclusions and theoretical recommendations are formulated to improve the practice of ensuring the financial stability of insurance companies.
Keywords: Insurance companies, insurance premium, insurance obligation, financial stability, insurance activities, ensuring stability, financial resources, investments.